Analytical Study of Non-Oil Foreign Trade on the Libyan Economy During the Period (2000-2019) (Al-Mukhtar Journal of Economic Sciences, 2021)
Foreign trade accompanied the economic policies that were set to achieve economic developments and these developments were reflected in the economic and social transformation plans that were implemented. The development of Libyan exports aims to activate and develop exports of non-oil products and services, and everything that would develop these exports, and increase the volume of Libyan exports comes from Reducing the cost of the burdens of export operations, in addition to proposing policies and legislation organizing and supporting the export process and encouraging marketing of local goods and services in foreign markets, given the lack of diversification of such exports The failure to open new markets for Libyan non-oil exports Which requires how to increase and develop these exports and to identify the obstacles they encounter, whether internal or external, and the research reached a set of results, the most important of which is that crude oil and its derivatives represent the largest share of Libyan exports. The contribution of crude oil reached 60.9% during the research period, and this phenomenon makes the national economy is vulnerable to the fluctuations that occur in the global oil markets, and the Libyan foreign trade is characterized by a high degree of commodity concentration, as the value of the commodity concentration index is not less than 94% during the research period and export, and the high degree of geographical concentration of Libyan exports and imports in the European Union and America as well as depend on them as a target for their exports and the origin of their imports. The deterioration of the net trade terms during the period (2000-2010) Was due to the drop in oil export prices and the rise in the prices of imported goods, but the value of the index tended to rise in favor of Libyan exports during the period (2011-2019) as a result of the increase in oil prices.
Keywords: Foreign Trade; Trade Openness; Commodity Concentration; Geographical Distribution of Goods